Pengaruh BTS Sebagai Brand Ambassador Terhadap Strategi Pemasaran Mcdonald's di Indonesia - Lysandra May Salsabilla; Adithya Dwijaya; Erwin Permana (MANAJEMEN, 2026)
This study examines the role of BTS as a brand ambassador in McDonald’s marketing strategy in Indonesia through the “BTS Meal” campaign. The research applies a qualitative single case study approach supported by netnographic analysis of consumer responses on social media and review of official campaign documents. Using Source Credibility Theory, the study analyzes credibility, attractiveness, and trustworthiness as determinants of consumer response. The findings reveal that BTS’s credibility and attractiveness strengthened emotional engagement, generated symbolic value within fandom communities, and increased purchase intention. The collaboration not only attracted significant market attention but also reinforced McDonald’s brand positioning within popular culture. These findings confirm that selecting a brand ambassador with a strong fan base can serve as an effective strategy in enhancing brand image and consumer loyalty.